Long term prospects for significant improvement in public sector finances - Ellis, C.F. (OECS CastriesLC, 1987)
Identifies areas for improving economic growth in the OECS emphasizing the tourism and agricultural sectors. Examines the complexities of fiscal linkages showing the relationship between improvement in public sector finances and greater tax compliance of the populace. Highlights anomalies in the financial operations of the public sector and suggests measures for improving finances. Expresses the need for proper management of public sector resources.